Cardiac Function Evaluation after SARS-CoV-2 mRNA Vaccination in Children and Adolescents: A Prospective Speckle-Tracking Echocardiography Study - Jolanda Sabatino; Costanza Di Chiara; Daria Lauretta; Jennifer Fumanelli; Greta Luana D’Ascoli; Daniele Donà; Sandra Cozzani; Andrea Oletto; Carlo Giaquinto; Giovanni Di Salvo (Vaccines, 2023)
Background: Possible cardiac impairment after SARS-CoV-2 mRNA vaccination is a common driver of parental vaccine hesitancy. We performed a comprehensive echocardiographic evaluation of biventricular function in vaccinated children with or without previous COVID-19 compared to healthy controls. Methods: We conducted a single-center, prospective, case–control study enrolling children and adolescents aged 5–18 years attending the pediatric clinic of the University Hospital of Padua from April to June 2022. Three months after receiving the primary mRNA vaccination or booster dose, the patients underwent a cardiac assessment, including standard echocardiography and speckle-tracking echocardiography (STE). A pre-pandemic historical cohort of age- and gender-matched healthy children were used as a control. Results: A total of 39 post-VACCINE cases (24, 61% female), mean age 12.6 ± 2.6 years (range 8–17), were enrolled in the study. Ninety percent (N = 35) of patients were previously healthy. No differences in left ventricular diameters, left ventricular ejection fraction (LVEF), and tricuspid annular plane systolic excursion (TAPSE) were observed between cases and controls. Global longitudinal strain (GLS) was in the normal range in all individuals, with no differences between post-VACCINE cases and controls (−21.7 ± 2.3% vs. 21.2 ± 1.8%; p = 0.338). However, GLS was found to be slightly but significantly reduced in post-VACCINE children with a previous COVID-19 compared to naïve-vaccinated individuals (post-VACCINE+COVID-19: −19.9 ± 1.1% vs. post-VACCINE-only: −22.0 ± 2.3%; p = 0.002). Conclusions: We did not observe an impairment in GLS or in other indices of LV structure or function after mRNA COVID-19 vaccination.